Web channels in Information Science: Media Documentation and Multimedia Production in Complumedia-RTVDoc - López Yepes, Alfonso; Cámara Bados, Víctor (Estudios sobre el Mensaje Periodístico, 2012)
This paper provides an overview of the training, research and multimedia production activities undertaken by the Servicio de Documentación Multimedia (Multimedia Documentation Service) of Computense University’s Department of Library and Information Science, in collaboration with Latin American universities and other institutions. These activities encompass E-learning, blended and campus-based teaching, and rely heavily on the Service’s web channel RTVDoc, which offers multimedia contents both real-time and on demand. In what follows, I will also analyse a number of current projects led by the Service. Firstly, the Doctoral programme Documentación: Fundamentos, Tecnologías y Aplicaciones (2008- 2010) (Information Science: Foundations, Technologies and Applications), taught by the said department through e-learning. Secondly, the creation in 2007 of a thematic web channel, Complumedia-RTVDoc, devoted to multimedia production and digital information management in the media. Reference will also be made to the endeavours of the Laboratorio multimedia de formación, investigación y producción en línea (Multimedia Lab for Online Training, Research and Production), also operated by the Servicio, as well as to E-Televisión and Cine@Tele Online, two other web channels devoted to digital information management in the media. As a result of this analysis, I will make a number of suggestions on possible developments in this line of research. Finally, an annex is provided with a sample videography which draws from files contained in Complumedia-RTVDoc.